ANALISA SWOT PADA PENGUATAN KELOMPOK TANI SAYUR ORGANIK - Nur Fauzi; Suswadi; K. Prasetyowati (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2020)
Nur Fauzi, B0216023. 2020. Argoayuningtani Farmer Group Development Strategy in Organic Tomato (Lycopersicon esculentum) Farming in Senden Village, Selo District, Boyolali Regency. Skripsi.Supervisor I Ir. Sutarno, M.Si, Supervisor II Ir. Suswadi, M.Si., Agribusiness Study Program, Bachelor, Tunas Pembangunan University of Surakarta. An organization must have a careful planning and strategy. Strategy is very influential on organizational development. This study aims to determine the internal and external factors that influence the development of Argoayuningtani farmer groups in organic tomato farming. Method research that is used is the analysis of SWOT to identify factors internal and external are then analyzed using matrix IFE, EFE, SWOT, IE, and QSP.The results of the study based on the analysis of the IFE matrix get the main strengths that are according to SOP/ GAP/ GHP and good quality Human Resources of members with a score of 0.268,while the main weakness is having a planting plan but not yet implementing it with a score of 0.118 and obtaining a total score of 2.941 means that the Argoayuningtani farmer group has a strong internal position. Based on the EFE matrix analysis, the main opportunity is the active role of the instructor with a weight score of 0.352 while the main threat is land adjacent to conventional land with a score of 0.252 and a total score of 3.021 means that the external position of the farmer group is above average. In IE matrix analysis Argoayuningtani farmer group is in cell II which means that Argoyuningtani farmer group is in a position of growing and developing. Whereas based on QSP matrix analysis, it is found that the priority of development strategies that can be applied in the Argoayuningtani farmer group is to improve human resource skills to realize the goals with the highest STAS value of 6.20.